Resource-dependent investment in male sexual traits in a viviparous fish. (23rd June 2022) - Fernlund Isaksson, Erika; Reuland, Charel; Kahrl, Ariel F; Devigili, Alessandro; Fitzpatrick, John L
Abstract: Exaggerated and conspicuous sexually selected traits are often costly to produce and maintain. Costly traits are expected to show resource-dependent expression, since limited resources prevent animals from investing maximally in multiple traits simultaneously. However, there may be critical periods during an individual's life where the expression of traits is altered if resources are limited. Moreover, costly sexual traits may arise from sexual selection acting both before (pre-copulatory) and after mating (post-copulatory). Gaining a robust understanding of resource-dependent trait expression therefore requires an approach that examines both episodes of sexual selection after resource limitation during different times in an individual's life. Yet few studies have taken such an approach. Here, we examine how resource restriction influences a set of pre- and post-copulatory traits in male pygmy halfbeaks ( Dermogenys collettei ), which invest in sexual ornaments and routinely engage in male–male contests and sperm competition. Critically, we examined responses in males when resources were restricted during development and after reaching sexual maturity. Both pre- and post-copulatory traits are resource-dependent in male halfbeaks. Body size, beak size, courtship behavior, and testes size were reduced by diet restriction, while, unexpectedly, the restricted-diet group had a larger area of red color on the beak and fins after diet treatment. These patterns were generally consistent when resources were restricted during development and after reaching sexual maturity. The study reinforces the role of resource acquisition in maintaining variation among sexual traits. Abstract : Hide Does going on a diet make animals worse at reproducing? Evolutionary theory suggests that reproductive success often depends on how good animal are in finding food and converting this energy into finding and attracting mates. We tested this idea in a small freshwater fish and show that males with access to less food are worse at courting females, have shorter jaws, and produce fewer sperm.